Here's the question you clicked on:
openstudyadmin
I can just plug them in and if they work, its right.. right? -x-4y=18 2x-4y=24 A.) (4,-5) B.) (-3,6) C.) (2,-5) D.) No Solution
i need someone too explain it too me step by step
just try to substitute the value for y in the main equation 3x+3(-2)=-2 3x-6=-2 3x=4 x=4/3 and you already have the value for y which is -2 then your order pair would be (x,y) which is (4/3,-2)
oh danget i meant y to eqaul -x ,but i understand same concept right?
K now im stuck. 3x+3(-x)=-2 3x-3x=-2 0?=-2 x=
0 is not equal to -2 then it has no solution